A simple molecular model to study the substrate diffusion into the active site of a lipase-catalyzed esterification of ibuprofen and ketoprofen with glycerol - Toledo, Victoria; Briand, Laura Estefania; Ferreira, María Luján (Topics in Catalysis)
Lipases are enzymes widely applied in the kinetic resolution of racemic non-steroidal anti-inflammatory drugs (NSAIDs). The esterification of racemic ibuprofen and ketoprofen with glycerol catalyzed by the lipase B of Candida antarctica (CALB) was performed by some of us, achieving very different results for both NSAIDs in terms of enzymatic activity, enantio- and regioselectivity. A molecular modelling investigation allowed to establish the steric energies and the enthalpy variations along the diffusion of glycerol through the enzymatic tunnel towards the active catalytic triad of the lipase along with the interaction with the acyl enzyme species. In this context, it was possible to demonstrate that glycerol approaching the acyl enzyme of the R-ibuprofen possesses lower steric hindrance than the S-ibuprofen acyl enzyme (− 185.3 vs − 188.6 kcal mol−1 for S and R-enantiomers, in average). Although, the steric energy is somehow similar when the acyl enzyme of the R/S-ketoprofen is considered (− 201 kcal mol−1) the proximity of glycerol to the aminoacid residues of the enzymatic tunnel towards the active site plays a key role. In fact, the closer distance of glycerol to the tunnel walls when the acyl enzyme of ketoprofen is present than ibuprofen (2.1 Å vs 2.9 Å) allows multiple H-bonding interactions between the polyol and the aminoacids and also increases the enthalpy of formation of glycerol?acyl enzyme species. Fil: Toledo, Victoria. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas "Dr. Jorge J. Ronco". Universidad Nacional de la Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Ciencias Aplicadas; Argentina Fil: Briand, Laura Estefania. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas "Dr. Jorge J. Ronco". Universidad Nacional de la Plata. ...